Persepsi Guru Matematika Terhadap Penggunaan Google Formulir Sebagai Alat Evaluasi Pembelajaran di Sekolah Dasar - Lutfia Maulida; Istiyati Mahmudah (JUMAT: Jurnal Matematika, 2023)
The presence of advanced technology in the current era makes learning evaluation also comes with digital-based, for example, Google Forms. From previous research, Google Forms has many advantages and is effectively applied. However, behind these advantages, of course, there are shortcomings found in Google Forms as a learning evaluation tool.  This study aims to determine the perceptions of mathematics teachers towards the use of Google Forms as a learning evaluation tool and to determine whether or not the use of evaluation through Google Forms in mathematics subjects is effective. The method in this research uses qualitative research. This research was conducted for one day, namely on 10 October 2023 and took place at SD IT Al-Furqan Palangka Raya. The research subject was 1 person, namely the fourth grade Maths Teacher. The instrument in this study was an interview guide. The results showed that the perception of mathematics teachers towards the use of Google Forms as a learning evaluation tool in elementary schools was not effective for their students. Because, when teachers give evaluations to students through Google Forms, they will be able to search first through Google.